(untitled) (TECHNO REVIEW. International Technology, Science and Society Review /Revista Internacional De Tecnología, Ciencia Y Sociedad, 2022)
The objective of this research is to review and compare the TAM/TAM2/TAM3 and the UTAUT/UTAUT2 through a bibliometric approach to determine which is the most appropriate model to study new technologies. Data was obtained from the Web of Science database. 2,450 publications were examined, related to TAM/TAM2/TAM3 and 5,145 publications of UTAUT/UTAUT2 during the period 2016-2021. The findings confirm that UTAUT/UTAUT2 is being used by more and more researchers. This review offers a holistic view that will help future researchers to select the most appropriate models in their disciplines of study.